Effectiveness of Homoeopathic Treatment in Haemorrhoids- An Observational Study (Advancements in Homeopathic Research, 2022)
Background & objectives Haemorrhoids are certainly one of the commonest  ailments that afflict mankind. Bleeding and prolapse  are the cardinal symptoms of haemorrhoids. Pain,  mucus discharge and Itching, are the other most  common complaints from the patients. This leads to  reduced work efficiency, quality of life and increased  financial burden on the patients. Homoeopathy is  reported to have a significant role in haemorrhoids in  both classical literature and recent studies. However,  its efficacy in the South Indian population has not yet  been reported. Thus, an effort has been made to find  out the effectiveness of Homoeopathic treatment in  haemorrhoids.  Methods In this prospective, observational study, conducted  at Fr. Muller's Homoeopathic Medical College and  Hospital, Mangalore during the year 2002-2003, on  patients of age groups between 20-75 years, based  on their clinical presentation such as bleeding, pain,  discharge, itching and examination. They were  treated with homoeopathic medicines, using disease  intensity scores as a parameter. This study protocol  was approved by the Institutional ethical committee  of Fr. Muller's Homoeopathic Medical College and  Hospital, Mangalore and consent was obtained from  the participants. All the patients were followed for a  minimum period of 3 months.  Results and Discussion A total of 30 patients were enrolled and analyzed  for the study. After treatment significant change  is found in bleeding, pain, pruritus ani, and mucus  discharge per rectum of the patients. However, no  change is found in Prolapse. Symptoms were graded ranging from 0-3 depending upon the severity of the  complaint. The sum of these grades were considered  before and after treatment for the patients. Most  frequently used medicines were Sulphur (n = 6),  Lycopodium (n = 5), Natrum mur (n = 4), Pulsatilla (n = 3) and Nux vomica (n = 3). The Statistical  analysis ‘t-test’ showed, that the calculated value  of 13.7 is greater than the tabled value of ‘t’ at the  5% level with 29 df (2.045). This shows the positive  effect of homoeopathic medicines in the treatment of  haemorrhoids.  Conclusion It is concluded that homoeopathic treatment is  effective in haemorrhoids, which is reflected in  significant reduction in symptoms of haemorrhoids,  as observed with the disease intensity score.
Keywords: Disease intensity score; Homoeopathy; Haemorrhoids; Homoeopathic medicines